Climate, landscape and cultural dynamics in the Colombian Caribbean: a multidisciplinary perspective on changes from the middle holocene to present (2020)
Colombian coastal lagoons and estuaries suffer from recent loss of ecological integrity. Crucial environmental services like hydrologic regulation and nutrient cycling are being curtailed or lost completely because of climate and environmental changes. The Caribbean region is extremely sensitive to modern alterations because of its position among the cores of the most significant atmospheric phenomena -e.g. El Niño–Southern Oscillation (ENSO), the Atlantic Multidecadal Oscillation (AMO), the South American Monsoon System (SAMS) force and position variations-, high population density and limited connection with the rest of the Atlantic. There are substantial knowledge gaps related to the spatial and temporal variability of coastal ecosystems responses to disturbance, its inner structure and functions. This needs to be alleviated to effectively design of preservation and restoration actions. The thesis is a contribution to such a challenge. Foreign and national contributors, my advisor and I developed a multidisciplinary reconstruction of the climate, landscape and cultural history of the Colombian Caribbean during the last ~7.6 millennia. Three sites along the Caribbean coast of Colombia were selected for this purpose, i.e. Caimanera, Totumo, and Las Quintas Lagoons. The sediment record spans about the last 7,400 years in Caimanera Lagoon, 7,600 years in Totumo Lagoon, and the last 800 years in Las Quintas Lagoon. Each lagoon history was inferred using some or all of the following sediment variables: lithology, fossil content, stable carbon and nitrogen isotopes, nutrients, inorganic carbon and Chlorophylla.